(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2015)
Globalization is the term used to describe, “The integration of the world economy through the expansion of trade, investment and financial flows, underpinned by the revolution in information and communications technology. New technologies have made it possible for money, goods, people, information and services to move quickly and efficiently around the world. Companies can make and sell products anywhere in the world, and they can have different parts of their company located in different parts of the world. Thus, the process of globalization is inevitable, flowing naturally from advances in communications, transportation, and other technological changes.